FLOOD DISASTER MITIGATION IN SONE DISTRICT, TANAH BUMBU REGENCY, SOUTH KALIMANTAN AS A SOURCE FOR LEARNING IPS CLASS VII - susanti susmindari (JURNAL SOCIUS, 2022)
AbstrakFlood disasters that occur in Satui District almost occur every year, in 2019 there were six villages affected by flooding in Satui District, the purpose of this study was to find out the causes of floods that occurred in Satui District, and the efforts of the government and the community in minimizing the risk of loss in dealing with floods. flood disaster or better known as disaster mitigation. Mitigation activities include preparation before a disaster occurs, handling when a disaster occurs, evacuating residents affected by floods, and socializing disaster mitigation after a flood which can be socialized through social studies education that specifically discusses social issues. This study uses a qualitative approach. Data collection techniques include; interviews, observations and documentation of data analysis starting from reduction, presentation, and verification. The results of the study illustrate that the flood disaster that occurred in Satui District, Tanah Bumbu Regency is caused because it is a lowland if high rainfall will cause flooding, the government's efforts in implementing mitigation have not been maximized so it is necessary to disseminate information to the community by making flood disaster mitigation a learning resource for social studies class. VII junior high school level.